Application of Topological Methods in the Development of Vehicle Components - Szabó, Kristóf (International Journal of Engineering and Management Sciences, 2023)
Many areas of the industry are characterized by continuous changes, which define new directions of development in product design. The development of computers and software, the spread of modern production tools and the development of material technology make it possible to expand traditional production technologies with modern processes. Integrated CAD systems have occupied their place in the product design and development process for decades, reforming classical design methods. Popular optimization procedures in integrated CAD systems, such as shape optimization, topological optimization and the new generative design process, provide effective solutions for design engineers in more and more industrial application areas. Experience shows that modern design methods can be used in many areas of industry. The appearance of metal powder printing and additive technology make it possible to test the designed prototypes or even to produce the final products. The following article aims to support the above with the help of a case study.